Material and Elastic Properties of Al‐Tobermorite in Ancient Roman Seawater Concrete. Issue 8 (28th May 2013) - Jackson, Marie D.; Moon, Juhyuk; Gotti, Emanuele; Taylor, Rae; Chae, Sejung R.; Kunz, Martin; Emwas, Abdul‐Hamid; Meral, Cagla; Guttmann, Peter; Levitz, Pierre; Wenk, Hans‐Rudolf; Monteiro, Paulo J. M.; et al.
<x xml:space="preserve">Abstract</x> The material characteristics and elastic properties of aluminum‐substituted 11 Å tobermorite in the relict lime clasts of 2000‐year‐old Roman seawater harbor concrete are described with TG‐DSC and 29Si MAS NMR studies, along with nanoscale tomography, X‐ray microdiffraction, and high‐pressure X‐ray diffraction synchrotron radiation applications. The crystals have aluminum substitution for silicon in tetrahedral bridging and branching sites and 11.49(3) Å interlayer (002) spacing. With prolonged heating to 350°C, the crystals exhibit normal behavior. The experimentally measured isothermal bulk modulus at zero pressure, K0, 55 ±5 GPa, is less than ab initio and molecular dynamics models for ideal tobermorite with a double‐silicate chain structure. Even so, K0, is substantially higher than calcium‐aluminum‐silicate‐hydrate binder (C–A–S–H) in slag concrete. Based on nanoscale tomographic study, the crystal clusters form a well connected solid, despite having about 52% porosity. In the pumiceous cementitious matrix, Al‐tobermorite with 11.27 Å interlayer spacing is locally associated with phillipsite, similar to geologic occurrences in basaltic tephra. The ancient concretes provide a sustainable prototype for producing Al‐tobermorite in high‐performance concretes with natural volcanic pozzolans.